A CREATION OF A NEW MODEL OF WOMEN’S COAT: Сoat modeling - Хожиев, Абдурахим (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Purpose: the purpose of the research is to create a new model of women's cloak based on the analysis of artificial leather materials, taking into account the demands and wishes of women. Methods: in this article, a new model was created by studying the origin, types, and patterns of women's cloaks for the spring-autumn season. Development of design and technological documents and drawings of women's cloak using the "M. Muller i syn" methodology. Results: multi-functional models of women's cloaks were created from artificial leather. raw materials were used. Conclusion: in the production of women's cloaks from artificial leather materials, innovations have been introduced to the currently available models and convenience for consumers has been created.